2020
DOI: 10.1007/s40430-019-2156-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of volume variation in a homogeneous prechamber ignition system in combustion characteristics and exhaust emissions

Abstract: Research on prechamber ignition systems has become increasingly frequent as they promote significant reductions in engineout emissions with low cost of implementation. In these systems, the combustion starts in an auxiliary chamber and flows through the interconnecting holes, in form of jets, to the main chamber, where it ignites the air-fuel mixture contained therein. Besides the air-fuel ratio, the geometry of the prechamber presents fundamental parameters that influence combustion characteristics and, conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Given the difficulties for traditional spark plugs to realize high-quality ignition and combustion in lean-burn environments [7], many new ignition systems were developed, including high-energy ignition systems, multi-point ignition systems, and pre-chamber jet ignition systems. Some studies showed that pre-chamber Turbulent Jet Ignition (TJI) is superior to conventional spark ignition in improving engine fuel economy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Given the difficulties for traditional spark plugs to realize high-quality ignition and combustion in lean-burn environments [7], many new ignition systems were developed, including high-energy ignition systems, multi-point ignition systems, and pre-chamber jet ignition systems. Some studies showed that pre-chamber Turbulent Jet Ignition (TJI) is superior to conventional spark ignition in improving engine fuel economy [8].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This adverse climate change mainly due to emissions from vehicles and compelling the whole world to make strong policies for the control of exhaust emissions from vehicles as transport sector is majorly responsible for deterioration of an environment. 6,7 These policy pacts embrace UN framework convention held in 1992, Kyoto protocol held in 1998, Copenhagen accord held in 2009, Doha amendment in 2012 and Paris agreement in 2015. 8 It is estimated that 95% of energy used in vehicles worldwide fulfilled by fossil fuels and the contribution of transport sector in deteriorating air quality is approximated up to 60%–80% of toxic environmental emissions.…”
Section: Introductionmentioning
confidence: 99%